(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The article analyzes the changes promoted by Law No. 13,467/2017 in article 2 of the CLT, specifically the inclusion of § 3, which requires proof of integrated interest and joint action for the characterization of an economic group. The author discusses the legislative evolution of the institute and the impact of recent STF jurisprudence, which requires the participation of group companies in the trial phase to be held liable in the execution phase. It concludes that, although the law aimed for clarity, the current interpretation may hinder the satisfaction of alimony credits. (Received: June 2025 | Accepted: September 2025).